The Association Between Cholecystectomy and the Risk for Fracture: A Nationwide Population-Based Cohort Study in Korea - Lee, Eun Ji; Shin, Cheol Min; Lee, Dong Ho; Han, Kyungdo; Park, Sang Hyun; Kim, Yoo Jin; Yoon, Hyuk; Park, Young Soo; Kim, Nayoung (Frontiers in Endocrinology, 2021)
Objectives To evaluate the risk of fracture in individuals with a history of cholecystectomy in Korean population. Methods Individuals (n = 143,667) aged ≥ 40 y who underwent cholecystectomy between 2010 and 2015 and the controls (n = 255,522), matched by age and sex, were identified from the database of the Korean National Health Insurance Services. The adjusted hazard ratio (aHR) and 95% confidence interval (CI) of fracture were estimated following cholecystectomy, and a Cox regression analysis was performed. Results The incidence rates of all fractures, vertebral, and hip fractures were 14.689, 6.483 and 1.228 cases per 1000 person-years respectively in the cholecystectomy group, whereas they were 13.862, 5.976, and 1.019 cases per 1000 person-years respectively in the control group. After adjustment for age, sex, income, place of residence, diabetes mellitus, hypertension, dyslipidemia, smoking, alcohol drinking, exercise, and body mass index, patients who underwent cholecystectomy showed an increased risk of all fractures, vertebral fractures, and hip fractures (aHR [95% CI]: 1.095 [1.059-1.132], 1.134 [1.078-1.193], and 1.283 [1.139-1.444] for all fractures, vertebral fractures, and hip fractures, respectively). The risk of vertebral fractures following cholecystectomy was more prominent in the young age group (40 to 49 y) than in the old age group (≥ 65 y) (1.366 [1.082-1.724] vs. 1.132 [1.063-1.206], respectively). However, the incidence of hip fractures following cholecystectomy was not affected by age. Conclusion Individuals who underwent cholecystectomy have an increased risk of fracture. In the younger population, the risk of vertebral fractures may be further increased following cholecystectomy.